The Effectiveness of School-Based Management at SMK Negeri 1 Kakas - Lukow, Nofrike I. N.; Masengi, Evi Elvira; Bulo, Laurens (Technium Social Sciences Journal, 2025)
This study aims to analyze the effectiveness of the implementation of School-Based Management (MBS) at SMK Negeri 1 Kakas and interpret the results of field findings by comparing them with educational management theory and national regulations, especially the Minister of Education, Culture, Research and Technology Regulation No. 47 of 2023 concerning School-Based Management at the Primary and Secondary Education Levels. The research method used was descriptive qualitative with data collection techniques through observation, in-depth interviews and documentation. The results showed that the implementation of MBS at SMK Negeri 1 Kakas has implemented the principles of school autonomy, participation, accountability, and transparency, although not yet fully optimized. Program planning based on vision, mission, and data has been carried out, but the participation of all stakeholders has not been evenly distributed. Organizing has been carried out with a relatively clear task structure, but coordination across work units still needs to be strengthened. Program implementation is quite active, supported by students’ initiatives in independent activities and the involvement of the business/industry world (DU/DI), although it still faces obstacles in the variation of teachers’ digital literacy and parents’ involvement. Program supervision and evaluation have been conducted, but the follow-up of evaluation results has not been integrated into the quality management cycle systematically. Supporting factors for the effectiveness of MBS in this school include the open and transformative leadership of the principal, the commitment of some teachers, and the support of the business/industry world (DU/DI). On the other hand, inhibiting factors include budget limitations, low parental confidence to get involved, and a collaborative work culture that has not been strongly established. The findings also show a gap between stakeholders’ understanding of the MBS concept and its implementation in the field. Although the majority of stakeholders have a positive perception of MBS, the practice of involvement in decision-making and program evaluation is still administrative and symbolic. Overall, the implementation of MBS at SMK Negeri 1 Kakas is going in the right direction, but its effectiveness has not been maximized. It is necessary to strengthen the active participation of stakeholders, increase the capacity of human resources, manage data-based resources, and develop a sustainable evaluation system to support more participatory, accountable and quality-based school management.